Message from the executive of the Commonwealth, transmitting a report of Wm. H. Peters, commissioner, appointed by the governor to make an inventory of property taken from the United States government, at the Navy yard, Gosport, and in and near Portsmouth, Virginia (LLMC-digital (Series), 1861)
Report of Comissioner Wm. H. Peters regarding the inventory of United States property seized at the Navy Yard and Harper's Ferry transmitted to the Convention by Governor John Letcher on November 30, 1861. Included in this report were the inventories of all public property taken at the Navy Yard on April 21, 1861, as well as the inventory of guns, machinery, tools, and stock taken at Harper's Ferry and the inventory sent to Fayetteville, North Carolina.